Multiple Streams/Critical Juncture Approach in E-Government Policy Implementation: A Study on SEMESTA Application - Ade Kurniawan; Raniasa Putra; Akhmad Mustain (ARISTO, 2026)
This study aims to analyze the implementation of the SEMESTA application policy in order to improve administrative efficiency in Ogan Ilir Regency. The research method used is descriptive qualitative research. Data collection techniques using interviews, observation and documentation. The technique of determining informants is purposive sampling and snowball sampling analysis. The data analysis technique uses descriptive data analysis by following the six stages of qualitative analysis according to Creswell. This research uses Michael Howlett's Multiple Streams policy implementation theory, which includes four streams, namely the problem stream, policy stream, political stream, and program stream. Findings based on interviews, observations, and official documents show that the implementation of the SEMESTA application policy is still not optimal. Based on the analysis, problem flow and political flow are the main drivers of the policy, while when viewed from the program flow analysis, the implementation of the SEMESTA application policy faces challenges such as employee resistance to using fake GPS applications, the absence of specific regulations governing the SEMESTA application, and limited technological infrastructure, especially related to internet signals in certain areas. This study recommends increasing training and socialization, infrastructure, making special regulations for the SEMESTA application and continuous evaluation to support the sustainability of the SEMESTA policy.